The effect of resistance training on the anxiety symptoms and quality of life in elderly people with Parkinson's disease: a randomized controlled trial - Ferreira, Renilson Moraes; Alves, Wilson Mateus Gomes da Costa; Lima, Tiago Alencar; Alves, Thiago Gibson Goçalves; Alves, Pedro Artur Madureira, Filho; Pimentel, Clebson Pantoja; Sousa, Evitom Correa; Cortinhas-Alves, Erik Artur (Arquivos de Neuro-Psiquiatria, 2018)
Objective: To assess the effects of resistance training on the anxiety symptoms and quality of life in patients with Parkinson's disease.Methods: Thirty-five elderly patients were randomly divided into two groups: 17 patients in the control group and 18 in the intervention group. All patients maintained standard pharmacological treatment for Parkinson's disease, but the intervention group participated in a 24-week resistance training program. The anxiety symptoms were assessed through the Beck's Anxiety Inventory, and quality of life by the Parkinson's Disease Questionnaire–39.Results: There was a significant reduction in anxiety level and increase in quality of life after 24 weeks of resistance training.Conclusion: The results of the present study indicate that resistance training is an effective intervention in the reduction of anxiety symptoms and improves the quality of life in elderly people with Parkinson's disease.
Keywords: resistance training; anxiety; Parkinson disease; randomized controlled trial